DELINEATION OF GROUNDWATER POTENTIAL ZONE IN THE INDO-GANGETIC PLAIN THROUGH GIS ANALYSIS (Journal of Institute of Science and Technology, 2017)
Water availability for domestic and irrigation purpose is the lifeline of the society and plays a dominant factor in the agriculture development of the country. Though Nepal is rich in water resources, nation-wide surface water irrigation network is yet to be established to meet the year round irrigation. The readily available shallow groundwater is considered as vital in meeting the domestic and irrigation water need. The shallow groundwater irrigation in the country has been emphasized and this system is contributing in the irrigation facility at present. Understanding the potential of shallow groundwater would support to further develop the shallow irrigation cluster wells in the Indo-Gangetic Plain. A systematic and comprehensive tube well database in GIS platform serves better for the groundwater potential delineation purpose. Thicknesses of aquifer material, well yield, hydraulic conductivity, water table are some of the decisive parameters for delineating the groundwater potential areas. However, all parameters are not always available. In such situation, the analysis can be performed with the thickness of aquifer material and yield of the well that are widely available in the reports of concerned organizations. Present study shows the GIS based analysis of aquifer parameters in one of the Terai districts of Nepal to delineate the shallow groundwater potential zones. The method adopted in the present study can be applied in other parts of the country, which would better serve for effective development planning and providing irrigation service to the farmers.Journal of Institute of Science and TechnologyVolume 22, Issue 1, July 2017, Page: 104-109